Optimizing design parameters of 3D‐printed poly‐4‐hydroxybutyrate nipple scaffolds for nipple reconstruction - Xue Dong; Sophia Salingaros; Timothy Butler; Skander Limem; Jason A. Spector (Bioengineering & Translational Medicine)
Abstract Nipple reconstruction in patients who undergo total mastectomy or nipple‐sparing mastectomy is currently limited by a consistent and significant loss of nipple projection over time, which can negatively affect patient satisfaction and quality of life. To address this issue, we have previously shown that 3D‐printed poly‐4‐hydroxybutyrate (P4HB) nipple‐shaped scaffolds promote long‐term maintenance of nipple projection in a rat model. Herein, we further optimize the 3D printing parameters (filament diameter and infill density) of absorbable P4HB latticework scaffolds as well as scaffolds fabricated from rolled P4HB knitted mesh to facilitate tissue formation with similar biomechanical properties of the native nipple, while maintaining long‐term shape and projection. Over 12 months of in vivo implantation in a dorsal, bilateral CV‐flap rat model of nipple reconstruction, 3D‐printed P4HB latticework and knitted mesh scaffolded groups demonstrated significantly greater maintenance in projection (80–100% of initial value) when compared to the Cook Biodesign® Nipple Cylinder (~40% of initial projection), resulting from the infiltration of healthy fibrovascular adipose tissue, which demonstrated biomechanical qualities that approached those of the native human nipple. Overall, our results demonstrate that using a 3D‐printed P4HB latticework and rolled P4HB knitted mesh scaffolds significantly improved long‐term results in our animal model of nipple reconstruction and hold promise for improving nipple reconstruction outcomes in future clinical practice.